PENGARUH METODE QUANTUM LEARNING TERHADAP KEAKTIFAN BELAJAR SISWA KELAS 5 DI SDK KARITAS II SURABAYA - Inisia, Agatha; Permana, Natalis Sukma (CREDENDUM: Jurnal Pendidikan Agama, 2021)
Based on the researcher's observations while undergoing internship practice at Catholic Primary School Karitas II, Surabaya, it was observed that the process of teaching and learning activities related to Catholic Religious Education subjects was still focused more on one method, namely the lecture method. The method is so far making the students are not so active and happy following the process of catholic religious education teaching. Based on the research problems, the researcher was trying to find out a particular method of teaching in order to improve catholic religious teaching and learning activities in a more active and happy manner. This method of teaching is so called the Quantum Learning method. This research aims to determine the significant influence of applying the Quantum Learning method for an active and happy learning process related to the Catholic Religious Education subject. The method used in the research is the Quasi Experimental Design in the form of Non-equivalent Control Group Design. The population of the study consisted of the students belong to the 5th grade of the catholic elementary Karitas II Surabaya. Data collection was done by using questionnaire technique. Research data was analyzed by applying the t-test method. The results of data analyzed indicated that there was a significant influence of the Quantum Learning method on students’ learning activity with a significance value of learning scored by 0.000. This is because the scored value of 0.00 is smaller than the table value scored by 0.05.